The Application of Tropical Architecture Principles for Sustainability in Residential Houses of Bandar Lampung, Indonesia - Viata Viriezky; Tri Seprianto; Puan Jati Megawati; Ahmad Baqir Adrian (Universitas 17 Agustus 1945, 2026)
The building construction sector accounts for 40% of global energy consumption, with a significant portion used for thermal comfort and lighting. As a tropical country, Indonesia faces challenges in achieving thermal comfort while utilizing natural lighting. An approach to addressing this issue is tropical architecture, a design strategy that adapts to the tropical climate to enhance user comfort. Meanwhile, residential development continues to grow with population expansion, making house design a crucial aspect as it is a primary need. Therefore, this study examines the implementation of tropical architecture principles in residential buildings and aims to enhance occupant comfort and energy efficiency sustainably. The research employs observation and literature review methods to identify and analyze the application of tropical architecture. Two landed houses in Bandar Lampung were selected as case studies. The findings indicate that combining effective natural ventilation strategies and balanced natural lighting can contribute to occupant comfort and reduce building energy consumption. Additionally, the infiltration areas and the rainwater utilization can help mitigate runoff and improve energy efficiency. This study contributes to sustainable house design concepts to be contextually suited for the tropical climate and offers practical recommendations for architects and developers to support environmentally friendly housing development.